How many meals should I eat each day? - Wendy Dahl; Zainab Alyousif (EDIS)
For older adults who want to stay healthy, it’s a common question. Should I eat three meals a day or is two meals adequate? Also, should I eat snacks between my meals? For healthy older adults, the number of meals may not matter as much as the total food eaten in a day. It is the nutritional quality of your meals and snacks and the total calories eaten that are most important. Aiming to meet the recommended servings of food groups, i.e. fruits, vegetables, grains, protein foods, and dairy will help promote good health and prevent illness.